Розробка та дослідження мікроструктури легких високоентропійних сплавів систем Al–Si–Cu–Ni–Zn та Al–Si–Cu–Ni–Mg–Zn - Ліхацький, І.Ф. (Physico-technological Institute of Metals and Alloys, 2025)
The study presents the results of the structural and phase characteristics of lightweight experimental Al–Si–Cu–Ni–Zn and Al–Si–Cu–Ni–Mg–Zn systems high-entropy alloys, obtained by the simplest method of melt preparation – melting in a resistance furnace using a covering flux. The purpose of the study was to establish the possibility and features of obtaining the specified compositions using the most accessible technological method of alloys preparation without the use of complex technological operations. The developed and tested technological sequence of melt preparation is described, which consists in melting the Al50Cu master-alloy and gradually and alternately adding all components to its melt in pure form. A gradual change in the chemical composition of the melt in this case increases the solubility of the components. The finished melt was obtained and poured into a mold within the temperature range of 950-1000 °С. In order to prevent the burning out of zinc and magnesium, especially at the last stages of the preparation of melts, a covering flux was used, which consisted of equal parts of lithium chloride and fluoride. The obtained alloys had a low density of 5.20 and 4.95 g/cm3 and were classified as high-entropy alloys in terms of their chemical composition. At the same time, they had a multiphase microstructure with a predominance of intermetallic compounds in it. The alloy that did not contain magnesium contained mainly β-CuZn and AlNi2Si–Al. After the addition of magnesium, an additional Mg2Si phase was formed, and the dominant phase was a complex intermetallic based on Cu-Mg-Si. Microhardness measurements showed high local values of 744 and 904 HV for both phases of the Al–Si–Cu–Ni–Zn system alloy and 730-780 HV for the Al–Si–Cu–Ni–Mg–Zn system alloy.